Structural insight of NICD-MAML interactions: virtual screening, docking and molecular dynamics study for the identification of potential inhibitor - Sinha, Noopur; Chowdhury, Saikat; Sarkar, Ram Rup (Letters in Drug Design & Discovery, 2016)
Activation of Notch signalling pathway is triggered by binding of NICD to transcription factor CSL and transcriptional co-activator MAML, which involves in various biological functions as well as progression of diseases. Recent prediction shows suppression of cancer causing genes of this pathway through inhibition of NICD-MAML interaction. Through virtual screening against ``NCI Diversity 3'' of Zinc database, we identified a potential inhibitor ``ZINC01690699'' (1-N,4-N-bis[3-(1H-benzimidazol-2-yl)phenyl]benzene-1,4-dicarboxamide; 1-N, 4-dicarboxamide) possessing highest binding affinity to block the two distinct Binding Sites of NICD to inhibit NICD-MAML interaction and also found the most imperative and essential Binding Site (Site I). Inhibition of this interaction caused by binding of ZINC01690699 is validated by protein-protein docking and the prolonged binding as well as stability of NICD-Inhibitor complex is supported by molecular dynamics simulation. The study not only identifies the best inhibitor but also proposes a potential drug for the treatment of cancers.
Keywords: free energy of binding; MAML; NICD; Notch signalling; potential inhibitor; ZINC01690699